Secularism in multi-religious Indian society - Tyagi, Ruchi (Deep and Deep, 2001)
1. The concept of secularism. 2. Secularism in ancient India. 3. The spirit of inherent unity of religions. 4. Echoes of secularism in modern India. 5. Gandhi's concept of secularism 6. Nehru's concept of secularism. 7. Secularism. Constituent assembly, constitutional provisions and parliamentary enactments. 8. Judicial interpretations of Indian secularism. 9. Aberrations of secularism. 10. Epilogue. The future of secularism